Campaign Strategy Drs. H. Amat Antono, M.Si On General Election 2006-2011 And 2011-2016 In District Pekalongan - meriyani sevtin ogesti; Sulityowati Sulityowati; Hermini S Hermini S (Journal of Politic and Government Studies, 2015)
Pekalongan Regency is one of the areas in Central Java that  carried out direct local elections of  Regent and Vice- Regent in 2006 the for  the first time. There are two pairs of candidates for Regent and Vice- Regent of Pekalongan, intersetingly  in this election is that the two candidates, namely Drs. H. Highly Antono, M.Si and Dra. Hj. Siti Qomariyah, MA. As it is known that Amat Antono and Siti Qomanyah who were the Regent and Vice- Regent of Pekalongan in the period 2001-2006 were selected through legislative in the election of 2006, Amat Antono was defeated by acquiring 48% of the vote, while Siti Qomariyah as elected Regent of Pekalongan acquired 52% of the vote.   In 2011, Pekalongan reimplemented direct election  for the second time. In the 2011 election, Amat Antono was the prospective Regent of Pekalongan. Antono was successfully be elected as Regent by acquiring 56,% of the vote. This study used a qualitative and descriptive methods. Data collecting is done by in-depth interviews with actor directly involved and also the bearer party and supporters. Beside, the study also used the data and documents to support the completeness of the information needed. The purpose of this study was to determine what  the strategy in the election campaign of 2006 and the election of 2011 was. Based on the research results, the strategies applied in the election campaigns of 2006 and 2011 were quite different. In the 2006 election campaign strategy is: first, the manufacture of campaign paraphernalia. Second, socialization of vision and mission. Third, the development of strategic issues. Fourth, the closed campaign reserved for a handful of people and was filled with a variety of political contract. Fifth, open campaign conducted in the field and enlivened by entertainment. In the 2011 election, campaign strategy used is as follows: First, the manufacture of campaign paraphernalia. Second, socialization of vision and mission. Third, the development of strategic issues. Fourth, build self-image. Fifth, the strategy of picking up the ball. Sixth, grand campaign (parade and entertainment).  Keywords: local Election, Campaign Strategy, Amat Antono